2013
DOI: 10.1002/app.39950
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic glazings for overheating protection. I. Material preselection, formulation, and light‐shielding efficiency

Abstract: This article presents a systematic strategy for formulation and optimization of thermotropic layers for overheating protection purposes. Specifically, thermotropic systems with fixed domains (TSFD) which consist of a thermotropic additive finely dispersed in a matrix material are considered. Based on systematic material (component) preselection regarding thermoanalytical characteristics and refractive indices, numerous thermotropic layers were formulated. TSFD with thermoplastic matrix were produced by compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 38 publications
(58 reference statements)
3
14
0
Order By: Relevance
“…For the annealed layers, the temperature-dependent behavior was inverted. Such kind of behavior was observed already in earlier studies [28][29][30]: TSFD without defects (like vacuoles or voids) showed a decrease in the solar hemispheric transmittance upon exceeding the threshold temperature. This behavior is consistent with the observed change in the relative refractive index (an increasing deviation from unity) between matrix and thermotropic additive upon exceeding the threshold temperature [28,30].…”
Section: Source Of Variationsupporting
confidence: 78%
See 4 more Smart Citations
“…For the annealed layers, the temperature-dependent behavior was inverted. Such kind of behavior was observed already in earlier studies [28][29][30]: TSFD without defects (like vacuoles or voids) showed a decrease in the solar hemispheric transmittance upon exceeding the threshold temperature. This behavior is consistent with the observed change in the relative refractive index (an increasing deviation from unity) between matrix and thermotropic additive upon exceeding the threshold temperature [28,30].…”
Section: Source Of Variationsupporting
confidence: 78%
“…The UV-curable resin matrix consisted of 57 wt% polyester acrylate oligomer Ebecryl 800 (Allnex Belgium SA/NV, former Cytec Surface Specialities, Drogenbos, Belgium), 40 wt% reactive diluent OTA-480 (OTA) -a propoxylated glycerol esterified with acrylic acid (Allnex) -and 3 wt% photobleaching photoinitiator Lucirin TPO-L (BASF SE, Ludwigshafen, Germany). The thermotropic additive was paraffin wax Sasolwax 5005 (additive A1; Sasol Wax GmbH, Hamburg, Germany) with a melting point of 55°C [28]. The nomenclature of the thermotropic additive is consistent with previous publications [28][29][30].…”
Section: Materials and Formulationmentioning
confidence: 98%
See 3 more Smart Citations